Assessment of sleep quality and correlates in a large cohort of Colombian women around menopause (2013)
Objective: The aim of this study was to determine the relationship between self-reported sleep quality, menopausal symptom intensity, and correlates (including ethnicity) among middle-aged women. Methods: The present cross-sectional study involved 1,078 Colombian women aged 40 to 59 years who completed the Pittsburgh Sleep Quality Index (PSQI), the Menopause Rating Scale (MRS), and a general questionnaire exploring sociodemographic data. Results: The median [interquartile range] age of the whole sample was 49.0 [9.0] years. Among the participants, 45.4% were postmenopausal, 57.2% had increased body mass index values, 13.9% were black, 20.7% had hypertension, 74.1% had a stable partner, and 3.8% used hormone therapy. The prevalence of poor sleep quality was 57.1% (PSQI global score Q5). Significant correlations between PSQI global scores and MRS total and subscale scores were found. Multiple linear regression analysis found that higher PSQI scores (poorer quality of sleep) correlated with higher MRS psychological and somatic subscale scores (more severe symptoms), smoking habit, and hypertension. Menopause status and black ethnicity were excluded from the final regression model. Conclusions: Despite study limitations, poor sleep quality is highly prevalent in this large middle-aged Colombian female sample and is related to menopausal symptom severity, tobacco use, and presence of hypertension.